2017
DOI: 10.1111/cxo.12399
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in Langerhans cell density of the cornea and conjunctiva in contact lens‐induced dry eye

Abstract: Background:The aim was to determine longitudinal changes in Langerhans cell density (LCD) in the human cornea and conjunctiva during asymptomatic and symptomatic contact lens wear. Methods: Twenty-five participants with contact lens-induced dry eye (CLIDE) and 35 without CLIDE (NO-CLIDE), diagnosed using a range of symptom questionnaires and objective tests (tear film break up, cotton thread tear test and corneal staining) were enrolled. The central cornea and nasal bulbar conjunctiva were examined using a Hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 34 publications
(71 reference statements)
1
45
1
Order By: Relevance
“…11 To be considered eligible for this study, participants were required to pass the DEQ-5 and at least one of the objective DE tests, according to the pass/fail scores shown in Table 1. The methods used during this study to assess DE and ocular surface staining have been reported in detail elsewhere 14 and are briefly described in Table 1.…”
Section: Dry Eye and Ocular Surface Assessmentmentioning
confidence: 99%
“…11 To be considered eligible for this study, participants were required to pass the DEQ-5 and at least one of the objective DE tests, according to the pass/fail scores shown in Table 1. The methods used during this study to assess DE and ocular surface staining have been reported in detail elsewhere 14 and are briefly described in Table 1.…”
Section: Dry Eye and Ocular Surface Assessmentmentioning
confidence: 99%
“…More recently, it has been proposed that discomfort may arise as a result of the intrinsically sub‐clinical inflammatory response of the eye to contact lens wear . Preliminary studies have demonstrated a link between the mobilisation of inflammatory cells and contact lens‐induced discomfort. The association between lens‐induced discomfort and the upregulation of inflammatory mediators in ocular tissues during lens wear is less clear …”
Section: Preserving Ocular Healthmentioning
confidence: 99%
“…Currently, the role of inflammation in contact lens discomfort is controversial . A recent study that longitudinally evaluated Langerhans cells, being antigen‐presenting immune cells, in the cornea and conjunctiva demonstrated an initial transient increase in the density of these cells in people experiencing contact lens‐induced discomfort; the same effect was not observed in asymptomatic contact lens wearers, suggesting a potential inflammatory component to the aetiology of the condition …”
Section: The Process Of Assessing the Tear Film And Ocular Surface Inmentioning
confidence: 99%